Price Elasticities of Demand for Imports and Exports: Industry Estimates for the U.S., The E.E.C. and Japan - Stone, Joe A. (The Review of Economics and Statistics, 1979)
Joe A. Stone, Price Elasticities of Demand for Imports and Exports: Industry Estimates for the U.S., The E.E.C. and Japan, The Review of Economics and Statistics, Vol. 61, No. 2 (May, 1979), pp. 306-312